Accounting Comparability and Economic Outcomes of Mandatory IFRS Adoption - Neel, Michael (Contemporary Accounting Research, 2017)
Abstract This study examines the associations between four economic outcomes of the 2005 mandatory adoption of International Financial Reporting Standards ( IFRS ) and concurrent changes in two important accounting constructs, accounting comparability and reporting quality. My primary purpose is to evaluate the relative importance of cross‐country accounting comparability and firm‐specific reporting quality in explaining previously documented increases in Tobin's Q, stock liquidity, analyst forecast accuracy, and analyst forecast agreement following IFRS adoption. Given that improvements in both comparability and reporting quality are primary stated objectives of the International Accounting Standards Board ( IASB ), it is important to understand their relative roles in shaping the information environment of financial statement users following IFRS adoption. Using 1,861 first‐time adopters in 23 countries, I find that firms with a larger improvement in comparability have larger increases in Q, liquidity, forecast accuracy, and forecast agreement following adoption, relative to other adopters. In contrast, improvements in reporting quality around adoption appear to have only a second‐order effect that is generally limited to Q effects among those adopters with concurrent improvements in comparability. These results are robust to alternative design and variable specifications. Finally, I continue to find these results for samples restricted to countries with weaker pre‐adoption institutional environments and countries that did not initiate proactive financial statement reviews, indicating that strong institutions and regulatory improvements are not driving the results. Overall, my results suggest that improvements in cross‐country accounting comparability played an important role in the previously documented economic benefits that accrued to 2005 mandatory IFRS adopters.